Highly selective and sensitive chemosensor based on 2, 3-diaminophenazine hydrochloride for the detection of cyanide in pure water and its application in plant seed samples. (2nd August 2018) - Yong, Bi-Rong; Wei, Tai-Bao; Qu, Wen-Juan; Lin, Qi; Zhang, You-Ming; Yao, Hong
Abstract : A 2, 3-diaminophenazine hydrochloride (Q1 ) shows a ultrasensitive visible and fluorescence response for cyanide in pure water via hydrogen bonding. Abstract : In this study, we prepared an efficient chemosensor based on 2, 3-diaminophenazine hydrochloride, and it exhibited good dissolvability in water; more importantly, it could act as an efficient chemodosimeter for the selective detection of CN − in pure water. Upon reacting with CN −, 2, 3-diaminophenazine hydrochloride (Q1 ) displayed a remarkable visible and fluorescence response simultaneously with significant changes in both absorption and fluorescence spectra. Furthermore, the absorption and fluorescence detection limits of CN − were 1.95 × 10 −7 M and 1.13 × 10 −9 M, respectively. For practical applications, test strips based on this chemosensor could serve as convenient CN − detection tools. The chemosensor was also successfully applied to the detection of CN − in plant seeds and several natural water samples.